Evaluating the Effectiveness of the Teaching Factory Learning Model in Leading Vocational Schools: A Case Study of Agribusiness, Food Crops, and Horticulture Programs - Irfan, Andi Muhammad; Romadin, Achmad; Putra, Iswahyudi Indra; Baharsyah, Nur Intan; Nawi, Mohd Zulfakar Mohd (Universitas Ahmad Dahlan, 2024)
Teaching Factory (Tefa) represents a transformative paradigm in vocational education, designed to immerse students in real-world industry settings within the school premises. By integrating practical training directly into the curriculum, Tefa ensures that students gain hands-on experience alongside theoretical knowledge, fostering a comprehensive skill set. This innovative approach not only enhances students' employability but also cultivates a deeper understanding of industry practices, ultimately equipping them with the competencies needed to thrive in their chosen fields. This research reviews the evaluation of the implementation of Tefa learning at leading vocational schools in the Food Crops and Horticulture Agribusiness Study Program. The research method used was evaluation, using interviews, observation, documentation, and questionnaire studies. Based on the results of evaluation research on the implementation of the teaching factory learning model in the food crop and horticulture agribusiness skills program at SMKN A and B, the following can be drawn: Evaluation of the context, input, process, and product components shows promising results with percentages of 85.4%, 83.7%, 86.3%, and 83.4%, respectively. The data showed the effectiveness of practical learning in achieving vocational education goals.